2023
DOI: 10.1097/xcs.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Augmented Reality Annotation for Surgical Education during Laparoscopic Surgery: Results from a Single-Center Randomized Controlled Trial and Future Aspects

Abstract: BACKGROUND: We developed an interactive augmented reality tool (HoloPointer) that enables real-time annotation on a laparoscopy monitor for intraoperative guidance. This application operates exclusively via verbal commands and head movements to ensure a sterile workflow. STUDY DESIGN: Purpose of this randomized controlled clinical trial was to evaluate the integration of this new technology into the operating room. This prospective single-center study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Advanced surgical trainees (senior residents and fellows) proctored with an interactive AR tool designed to enable real-time annotation on a laparoscopy monitor for intraoperative guidance also showed improved surgical performance in elective laparoscopic cholecystectomies. This study demonstrated a decrease in the rate of classic, but misleading, corrections done by the surgical attendings in the AR group 33 …”
Section: Augmented Realitymentioning
confidence: 52%
“…Advanced surgical trainees (senior residents and fellows) proctored with an interactive AR tool designed to enable real-time annotation on a laparoscopy monitor for intraoperative guidance also showed improved surgical performance in elective laparoscopic cholecystectomies. This study demonstrated a decrease in the rate of classic, but misleading, corrections done by the surgical attendings in the AR group 33 …”
Section: Augmented Realitymentioning
confidence: 52%